Multilateralismus in Ostasien-Pazifik: Probleme und Perspektiven im neuen Jahrhundert - Maull, Hanns W.; Nabers, Dirk (Mitteilungen des Instituts für Asienkunde, Hamburg, 2001)
ASEAN -- East-Asian Economic Caucus -- ASEAN Regional Forum -- Korean Peninsula Energy Development Organization -- Asia-Pacific Economic-Co-operation -- Asia-Europe Meeting
Enth. 6 Beitr.. - Literaturverz. S. [231] - 236
Keywords: Korean Peninsula Energy Development Organization; East Asian Economic Caucus; Association of South-East Asian Nations -- Regional Forum; Asia -- Foreign economic relations; Pacific Area -- Foreign economic relations; Asia -- Foreign relations; Pacific Area -- Foreign relations; Ostasien; Südostasien; Graue Literatur; Aufsatzsammlung; Internationale Kooperation; Asiatisch-Pazifischer Raum